The Effectiveness of Green Open Spaces in Absorbing Carbon Dioxide Emissions in the Area of PT. Pelabuhan Indonesia (Persero) Regional 3 Subregional Jawa - Fadila, Isna; Tri Martiana; Abdul Rohim Tualeka; Arya Zulfikar Paramarta (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: Green spaces serve as various ecological purposes, most notably the removal of pollutants. Although PT. Pelabuhan Indonesia (Persero) Regional 3 Subregional Jawa was estimated to have quite significant carbon dioxide (CO2) emissions, the company had provided green open space in multiple locations. Calculating the effectiveness of green open spaces in absorbing CO2 emissions in the area of Pelindo Subregional Jawa was the aim of this study. Methods: The primary data used was observation, and secondary data were gathered through document and literature studies. The dependent variable was the calculation of carbon dioxide emissions, while the independent variable was the effectiveness of green open spaces (land cover types and green open spaces area). The IPCC 2006 equations were used for data analysis. Results and Discussion: The estimated carbon dioxide emissions at Pelindo Subregional Jawa came from the following sources: 1,945.51 tons from electricity consumption; 1,845.97 tons from ships; 1,102.30 tons from operational, employee, and passenger vehicles; and 4.49 tons from genset usage. That amounted to 4,898.27 tons per year overall. Based on the calculation, it was found that the green open space could absorb 4,434.94 tons of CO2 per hectare annually. Conclusion: The existing green open spaces in the area of Pelindo Subregional Jawa were not enough to absorb CO2 emissions, as CO2 emissions still left a residual of 463.33 tons/year.